HEPATITIS B SEROLOGY PROFILES ON CHILDREN AGED 1â13 YEARS OLD IN SUMENEP, MADURA - Putera, Edward M; Marcia, Dian; Firdarini, Itja; Amin, Mochamad; Juniastuti, Juniastuti; Purwono, Priyo B; Utsumi, Takako; Lusida, Maria I (Indonesian Journal of Tropical and Infectious Disease, 2012)
Background: Hepatitis B virus (HBV) which was acquired during perinatal or childhood would promote hepatocellular carcinoma with even higher percentage than that which was acquired during adult age. That is why HBV represents a serious public health threat for children. HBV vaccination has been integrated into national expanded programme on immunization (EPI) since 1997. The aimof they study is to investigate the prevalence of HBV among children who were born after 1997 in Sumenep. Material and Methods: a total of 102 children who were born after 1997 were enrolled in this study. All children were admitted in the Emergency Room and Pediatric Ward of dr. H. Moh Anwar General Hospital for some reasons. Written informed consents were obtained from parents/guardians of all the children. Study protocol was reviewed and approved by the Ethics Committees. All of these cases were examined for hepatitis B surface antigen (HBsAg), antibody to HBsAg (Anti-HBs), and antibody to hepatitis B core antigen (Anti-HBc). Result and Discussion: Overall, 6 (5.88%) of 102 samples were positive for HBsAg, 51 (50.00%) of 102 samples were positive for anti-HBs, and 49 (48.04%) of 102 samples were positive for anti-HBc. All the children were born after 1997. Conclusion: HBsAg rate is still high even after universal vaccination program, acquired protective antibodies against hepatitis B surface antigen were sufficient, but there is a suspicion for occult hepatitis B infections (OBI). A further study to confirm OBI is needed.